Towards industry 5.0 in disaster mitigation in Lombok island, Indonesia - Sukmono, Filosa Gita; Junaedi, Fajar (Jurnal Studi Komunikasi, 2020)
A recent natural disasters that gained extensive news coverage and public concern in Indonesia is the earthquake that occurred in Lombok Island, West Nusa Tenggara Province, in early August. Initially, local authorities stated that the earthquake on Lombok Island on 5 August 2018 was at an M 6.8 scale. However, the scale was later revised to M 7.0. This research used descriptive-qualitative case study method. Research result proved that the technological advances that have brought human civilisation to Industry 4.0 have a significant contribution to disaster mitigation. In the disaster that occurred in West Nusa Tenggara, researchers found that the government, disaster mitigation and recovery agencies, journalists, and the public used internet chat-based digital technology to conduct effective coordination. However, Industry 4.0 technology still has limitations in terms of disaster mitigation. Researchers suggest that the issues be addressed using industry 5.0, a technology based on the internet of things.